(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
The text discusses the Extension Project “Art in the Square: artistic experiences with women”, linked to the Federal University of Grande Dourados, which sought to provide access to culture and artistic practices, in connection with the challenges of the lives of women from the periphery of Dourados - MS. The account of feminist experimentation is divided into three moments, being a general presentation of the Project; subsequently, reflections on the practices of interdisciplinarity, horizontality, and aspects of audience formation in Workshops, Conversation Circles and Show Shows; and considerations about collective learning spaces in the face of the violence of modernity.